Microbial biomass protein from coconut residue using Rhizopus oligosporus - Ramos, Ana Marie T.; De Leon, Sonia Y. (1993.)
The objectives of this study are to determine the effect of increased surface area; to determine the initial volume of spore suspension and, to determine the effect of the length of fermentation, factors that will significantly increase protein content of coconut residue "sapal" Four different water to spore volume ratio of the spore organism, Phizopus oligosporus were inoculated to the sapal substrate. It was found that an increased surface area significantly increased the protein content. Also, the best water to spore suspension volume ratio that produced the highest protein content was 0.50:1 at 13.91 from 6.39 after only twenty-four hours of fermentation.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Single cell proteins; Coconut residue